Hydrophobic hybrid silica sol-gel coating on aluminium: Stability evaluation during saturated vapour condensation - Maria Basso; Elena Colusso; Marco Tancon; Stefano Bortolin; Matteo Mirafiori; Massimo Guglielmi; Davide Del Col; Alessandro Martucci (Journal of Non-Crystalline Solids: X, 2023)
Hydrophobic coatings are widely employed in liquid-vapour phase change applications, offering advantageous control on condensation dynamics. However, they suffer from poor stability under harsh conditions and their durability is often neglected over thermal performance. Here, the global performance of a hybrid octyl-modified silica coating on aluminium was studied during saturated vapour condensation, in terms of thermal efficiency and durability. The coating successfully promoted dropwise condensation with heat transfer coefficients of ∼90 kW m−2 K−1, an average 9-fold increase with respect to filmwise condensation under similar heat flux conditions. Straightforward and reproducible tests were employed to separately evaluate the different factors influencing the coating's degradation, attempting to reproduce the conditions present in the apparatus used for the condensation experiments. The developed tests could successfully provide a rapid estimation of the coating's durability during a broad range of liquid-vapour phase change applications.